2021
DOI: 10.1016/j.celrep.2021.109638
|View full text |Cite
|
Sign up to set email alerts
|

Long-term depression links amyloid-β to the pathological hyperphosphorylation of tau

Abstract: Summary In Alzheimer’s disease, soluble oligomers of the amyloid-β peptide (Aβ o ) trigger a cascade of events that includes abnormal hyperphosphorylation of the protein tau, which is essential for pathogenesis. However, the mechanistic link between these two key pathological proteins remains unclear. Using hippocampal slices, we show here that an Aβ o -mediated increase in glutamate release probability causes enhancement of synaptically evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 79 publications
(125 reference statements)
2
23
0
Order By: Relevance
“…Pyramidal neurons in hippocampal CA1 area is one of the fields that p-Tau first appears during Braak stage II of AD (Braak et al ., 2006). Although LFS-triggered tau phosphorylation at Ser396 (Kimura et al ., 2014; Regan et al ., 2015) and Ser202/Thr205 (Taylor et al ., 2021) in hippocampal slices has been previously reported, the effects of LTD-inducing LFS on the expression of p-Tau181, p-Tau217, and p-Tau231, recently proposed to be particularly sensitive markers of early AD, have yet to be described. Having developed stimulation protocols to reliably induce LTD at CA3 to CA1 synapses in live rats (Hu et al ., 2014; O’Riordan et al ., 2018a, b; Ondrejcak et al ., 2019), we confirmed (Hu et al ., 2014) that this protocol (LFS-900, 900 pulses at 1 Hz) triggered a robust persistent form of LTD that, like certain forms of long-term memory formation, is protein synthesis-dependent ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyramidal neurons in hippocampal CA1 area is one of the fields that p-Tau first appears during Braak stage II of AD (Braak et al ., 2006). Although LFS-triggered tau phosphorylation at Ser396 (Kimura et al ., 2014; Regan et al ., 2015) and Ser202/Thr205 (Taylor et al ., 2021) in hippocampal slices has been previously reported, the effects of LTD-inducing LFS on the expression of p-Tau181, p-Tau217, and p-Tau231, recently proposed to be particularly sensitive markers of early AD, have yet to be described. Having developed stimulation protocols to reliably induce LTD at CA3 to CA1 synapses in live rats (Hu et al ., 2014; O’Riordan et al ., 2018a, b; Ondrejcak et al ., 2019), we confirmed (Hu et al ., 2014) that this protocol (LFS-900, 900 pulses at 1 Hz) triggered a robust persistent form of LTD that, like certain forms of long-term memory formation, is protein synthesis-dependent ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicate that p-Tau396 can be enhanced by LFS-900 (1 Hz) in acute hippocampal slices (Kimura et al ., 2014; Regan et al ., 2015). In contrast, no change in p-Tau202/205 was triggered by LFS except under the extreme condition of 2 hours LTD induction over a period of 7 days in slice cultures (Taylor et al ., 2021). The experimental conditions used to detect changes in p-Tau396 in hippocampal slices differ very significantly from our live brain studies, including relatively young age and non-physiological temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity-dependent persistent increases and decreases in synaptic strength, long-term potentiation (LTP), and long-term depression (LTD), respectively, are the main forms of synaptic plasticity in the hippocampus and are used to study the neurophysiological substrates of normal learning and memory function [27,28]. Interestingly, recent studies indicate that LTD induction enhances tau phosphorylation at Ser396 (p-Tau396) [29,30] and, when repeated chronically, Ser202/Thr205 (p-Tau202/205) [31] in hippocampus in vitro. It is still unknown whether the expression levels of p-Tau181, p-Tau217, and p-Tau231 can also be enhanced by physiological LTD induction.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Most of the studies use synthetic Aβ oligomers to probe the role of tau in AD in acute slices. It was found that sAβ induced LTP block and LTD induction in rodent hippocampal slices via NMDAR-dependent hyperphosphorylation of tau by GSK-3 [ 97 , 98 ]. Oligomers of sAβ also induced tau dysfunction in acute human brain slices [ 99 ], and in all of the studies mentioned, the concentration of peptides was in the 100–500 nM range.…”
Section: Biological Effects Of Aβ In Vitro and In Vivomentioning
confidence: 99%